INFLUENCE OF INTEREST, PRICE, PRODUCT QUALITY, PROMOTION, AND BRAND IMAGE ON PURCHASING DECISIONS IN TRAVELOKA APP - Tanggor Sihombing; Dosma Sihombing (Ultima Management : Jurnal Ilmu Manajemen, 2021)
Abstract - This research was conducted to test and analyze the influence of interest, price, product quality, promotion, and brand image on purchasing decisions. The method used in this research was Structural Equation Modeling (SEM) using the SmartPLS application. The population in this study consisted of Traveloka application users with a total of 137 respondents. The study used purposive sampling with 104 respondents. The test results show that interest variable has a positive and significant effect toward purchasing decisions of Traveloka application users, while the price, product quality, promotion, and the variables of brand image have no significant effect toward users purchasing decisions of Traveloka application. Keywords: Price; Product Quality; Promotion; Brand Image; Interest